METHODOLOGY FOR RESTRUCTURING INFORMATION RESOURCE DATA TO IMPROVE THE EFFICIENCY OF STATISTICAL CODING - Тупиця, Іван Михайлович (Science-based technologies, 2019)
In modern coding algorithms, "data restructurings" are actively used for a more favorable representation of coded data. Under this notion is the transformation of the source data into a more convenient form in order to increase the efficiency of the representation of coded data. The article discusses issues related to the development of a new approach to data restructuring in order to improve the efficiency of statistical coding from the standpoint of increasing protection and reducing the length of information presentation. Existing data restructuring methods of the information resource, which are used to better present the coded data, are investigated. The disadvantages of external data restructuring methods that are actively used in modern information coding algorithms are analyzed. A fundamentally new approach to the restructuring of information resource data has been developed - internal restructuring, which is to identify patterns in the internal structure of message elements by a quantitative attribute. The requirements for the quantitative trait are analyzed. A comparative analysis of existing data restructuring methods is carried out. To improve the efficiency of statistical coding from the standpoint of reducing the length of the presentation of information and improve the protection of the information resource, it is proposed to use the method of internal restructuring of data by quantitative attribute. The determined direction induces the further development of the concept for the formation of a quantitative trait for using the method of internal restructuring of the data resource in statistical coding methods in order to increase the efficiency of statistical coding from the point of increasing security and reducing the length of the presentation of information.